Memoirs of the Bashaw Count Bonneval : from his birth to his death: shewing, the motives which induced him to quit the Service and Dominions of France; his Entrance into and sudden Rise in the Imperial Armies; his Exploits in Italy, Hungary, &c. his Quarrel with the Marquis de Prie, and its Consequences; the true Cause of his Disgrace at the Court of Vienna; and the Reasons which occasioned him to seek an Asylum amongst the Turks; with his various Fortunes, while in the Service of the Porte. Interspersed throughout with an entertaining Diversity of Secret Intrigues, Amorous Adventures, Military and Political Achievements; being, in effect, the Secret History of Europe for the best Part of the current Century. Written by himself, and collected from his papers. - Ahmed Paşa, Humbaracı, 1675-1747. (London)
x, 200, 326 s.